The lonely lake monster - Selfors, Suzanne (Little, Brown and Company, 2013)
"Ten-year-olds Pearl and Ben find excitement in the small town of Buttonville as they encounter otherworldly animals, including a lake monster, during their first official day as apprentices to Dr. Woo, a veterinarian for Imaginary Creatures"
Keywords: Imaginary creatures; Veterinarians; Apprentices; Jugendbuch